Hubungan Riwayat Status Gizi Ibu Saat Hamil Dengan Berat Badan Lahir - Eka Deviany Widyawaty (2019)
Nutritious food intake in pregnant women was necessary for maternal and fetal conditions remain healthy by providing enough food containing carbohydrates and fat as an energy source. Growth and development of the fetus in the womb was affected by several factors such as the nutritional status of the mother during pregnancy and maternal health factors during pregnancy. Lack of maternal nutritional status during pregnancy is one of the triggers of cases of babies with low birth weight. The purpose of this study was to determine the relationship history of maternal nutritional status during pregnancy based on indicators LILA by BBL in Puskesmas Patianrowo Nganjuk 2017.This research was an analytic study with cross sectional design. The population of this research was all postpartum mothers in Puskesmas Patianrowo Nganjuk 2017. Sampling was done by using simple random sampling of a number of 49 respondents. Data collection using observation sheet. The independent variable is a history of maternal nutritional status during pregnancy, while the dependent variable is the BBL. To analyze the relationship Chi-Square test was used with significance level ɑ = 0.05.The results showed that pregnant women who nourished a number of 45 respondents (91.8%) and well-nourished less number of 4 respondents (8.2%). From the results of analysis using Chi-Square test resulted in p - value = 0.000, then the p - value ≤ ɑ = 0.05 so that H0 is rejected.It can be concluded that there is a relationship between a history of maternal nutritional status during pregnancy with BBL in Puskesmas Patianrowo Nganjuk 2017. This research is expected postpartum mothers can share information and knowledge on the relationship of maternal nutritional status during pregnancy with BBL, especially to a mother of reproductive age in order to prepare for pregnancy early on.